2005
DOI: 10.2325/jbcs.12.288
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of seroma in breast cancer

Abstract: There is considerable variability in the way seroma is defined across studies, and its pathophysiology remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
19

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 29 publications
2
102
0
19
Order By: Relevance
“…Another factor is the presence of metastatic lymph nodes (9,32,38,39). The number of metastatic lymph nodes remains controversial because some studies found significant seroma formation, and others showed an insignificant association, similar to our study (10, 11, 24-29).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another factor is the presence of metastatic lymph nodes (9,32,38,39). The number of metastatic lymph nodes remains controversial because some studies found significant seroma formation, and others showed an insignificant association, similar to our study (10, 11, 24-29).…”
Section: Discussionsupporting
confidence: 85%
“…Breast size is another important factor (9,32,38,39). Wide chest wall dissection influences seroma formation (14).…”
Section: Discussionmentioning
confidence: 99%
“…8 Age, tumor size, surgical technique, the use of electrocautery (EC), preoperative chemotherapy and many other factors may affect the seroma formation. [9][10][11] It is claimed that, the use of EC increases seroma formation due to the tissue ischemia. 12 PEAK PlasmaBlade (PB) (Peak surgical inc. CA,USA), is an electrosurgical device that uses radiofrequency energy in short pulses via an insulated cutting electrode, and creates an effective cutting edge while the blade stays near body temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Латеральный кожный лоскут подшивают к бо-ковой поверхности передней грудной стенки (рис. 4,5). Рана послойно ушивается с оставлением активных дренажей (рис.…”
Section: материалы и методыunclassified
“…Лидирующая роль в развитии постмастэктомиче-ского синдрома принадлежит лимфорее [4,5], которая способствует формированию лимфоцеле, возникно-вению местных осложнений (краевой некроз, инфи-цирование), истощает больного и приводит к отсрочке адъювантной терапии, а также сопровождается более длительной госпитализацией и увеличением количе-ства амбулаторных посещений [6].…”
unclassified